2020
DOI: 10.14740/jocmr4062
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomical Characteristics of Corona Mortis: A Systematic Review of the Literature and Its Clinical Importance in Hernia Repair

Abstract: Background: Inguinal hernia repair is one of the most common daily operations in general surgery. However, the anatomical structures of the region, such as the corona mortis (the crown of death), make this procedure quite challenging. A comprehensive knowledge of its anatomy is essential, since massive hemorrhage may occur if the vessel is injured. The current review of the literature aimed to report the frequency and anatomical variations of vascular corona mortis. Methods: A substantial study was coordinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Classically, CMOR is defined as an arterial anastomosis between the external iliac system and OA (arising from the internal iliac); however, there may also be venous interconnections and/or replaced OA (arising from either the external iliac or inferior epigastric, as in our study). Two recent meta-analyses have reported prevalence of the corona mortis to be 46 and 49.3%, respectively, 22,27 with arterial CMOR at 25% in the Noussios et al's study and 17% in the Sanna et al's study. Notably, most of the included studies in the meta-analyses were based on cadaver dissections, which may limit findings due to vascular disease or prior surgery.…”
Section: Discussionmentioning
confidence: 89%
“…Classically, CMOR is defined as an arterial anastomosis between the external iliac system and OA (arising from the internal iliac); however, there may also be venous interconnections and/or replaced OA (arising from either the external iliac or inferior epigastric, as in our study). Two recent meta-analyses have reported prevalence of the corona mortis to be 46 and 49.3%, respectively, 22,27 with arterial CMOR at 25% in the Noussios et al's study and 17% in the Sanna et al's study. Notably, most of the included studies in the meta-analyses were based on cadaver dissections, which may limit findings due to vascular disease or prior surgery.…”
Section: Discussionmentioning
confidence: 89%
“…A recent systematic review of literature has reported the prevalence up to 46%. 39 This anastamosis is encountered during intra-pelvic approaches to acetabulum and may causes serious bleeding if injured. In current study no patient encountered corona mortis injury.…”
Section: Discussionmentioning
confidence: 99%
“…The topic has already been addressed in different types of studies such as bibliographic reviews ( 8 , 9 ), case reports, cadaver dissections, studies based on image examination ( 10 - 12 ), and surgeries ( 13 , 14 ). There is a lack of consensus regarding some aspects of CM , resulting from contradictory data among different studies.…”
Section: Introductionmentioning
confidence: 99%